PENGARUH PRODUK, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN ANGGOTA UNTUK MENABUNG (Survei pada Anggota KSPPS Bina Insan Mandiri Cabang Jeruksawit Karanganyar) - Retno Susanti, Fitroh Saibantono, Rahayu Triastity & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
This research aims to analyze the significance of the influence of products,promotion and quality of service of the decision of the members to save money onKSPPS Bina Insan Mandiri Branch Karanganyar and Jeruksawit analyze the dominantvariables its influence on the decisions of members to save money on KSPPS Bina InsanMandiri Branch Jeruksawit Karanganyar. This study used a survey method, the type ofdata the data used was qualitative and quantitative data, the source data used theprimary data and secondary data. The population in this study are all members of theKSPPS Bina Insan Mandiri Branch Karanganyar Jeruksawit a number of 1,284members, with as many as 100 samples of respondents, with incidental use of samplingtechniques in sampling. Technique of data analysis used the test of validity, reliabilitytest, test the assumption of linear regression analysis, classic double, t test, F test andcoefficient of determination. The research results obtained the conclusion that there is asignificant influence on products, promotions and quality of service of the decision of thesaving. Variable product is the dominant variables affect the decisions of members tosave, this is because the KSPPS Bina Insan Mandiri Branch Karanganyar Jeruksawithas a range of savings products.Keywords: product, promotion, quality of service, the decision to save